Demographic estimates of hunter–gatherers during the Last Glacial Maximum in Europe against the background of palaeoenvironmental data. (15th December 2016) - Maier, Andreas; Lehmkuhl, Frank; Ludwig, Patrick; Melles, Martin; Schmidt, Isabell; Shao, Yaping; Zeeden, Christian; Zimmermann, Andreas
Abstract: During the Last Glacial Maximum, ca. 25, 000 to 20, 000 calBP, the settlement remains of European hunter-gatherers show a patchy pattern with clusters of sites in some regions and no reported settlement in others. Using a density-based upscaling approach, we calculate regionally differentiated population densities. To test our results and assess possible biases, we compare the spatial distribution of sites against environmental preference scores derived from palaeoclimate model data and loess/forest distributions. We find pronounced demographic differences between Western Europe and eastern Central Europe that coincide with different environmental preferences: cool temperate conditions in the West as opposed to colder and drier conditions in the East. Comparatively few people and an adaptation to cold and dry conditions eventually may have led to an extinction of the local population in western Central Europe around 22, 000 calBP.